CLASSICAL EDUCATION, CLASSICAL LANGUAGES, CLASSICAL STUDIES (Annual of the Faculty of Philosophy in Skopje, 2021)
The Republic of North Macedonia is a country with rich and unique classical antiquity heritage and more than 75 years old tradition of classical languages and classical culture studies at all levels of education. Nevertheless, it is evident that the interest in enrolling in the Institute of Classical Studies has been decreasing for several years already.Different factors may be responsible for this. The present article presents and analyses the data from the survey conducted with fourth-year High school – Gymnasium students in the Republic of North Macedonia, whose goal was to investigate the relation between the interest in studying classical philology and the status of classical languages in high schools, the degree of awareness and perception of high school students of classical languages and classical studies as well as their motivation for choosing a particular university degree in general.The results of the survey show that high school students’ awareness, perception of the importance of classical education, and motivation for studying are in correlation with attending classical language classes, and there is an opportunity for the Institute of Classical Studies to address them directly in the future by creating appropriate policies.
Keywords: Classical education; Classical languages; Classical studies